Effect of Intracuff Lidocaine on Postoperative Sore Throat and the Emergence Phenomenon: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. - Fai Lam; Yu-Cih Lin; Hsiao-Chien Tsai; Ta-Liang Chen; Ka-Wai Tam; Chien-Yu Chen (PLoS ONE, 2015)
Background Postoperative sore throat and other airway morbidities are common and troublesome after endotracheal tube intubation general anesthesia (ETGA). We propose lidocaine as endotracheal tube (ETT) cuff inflation media to reduce the postintubation-related emergence phenomenon. Methods We searched PubMed, EMBASE, and Cochrane databases systematically for randomized controlled trials (RCTs) that have investigated the outcome of intracuff lidocaine versus air or saline in patients receiving ETGA. Using a random-effects model, we conducted a meta-analysis to assess the relative risks (RRs) and mean difference (MD) of the incidence and intensity of relevant adverse outcomes. Results We reviewed nineteen trials, which comprised 1566 patients. The incidence of early- and late-phase postoperative sore throat (POST), coughing, agitation, hoarseness, and dysphonia decreased significantly in lidocaine groups, with RRs of 0.46 (95% confidence interval [CI]: 0.31 to 0.68), 0.41 (95% CI: 0.25 to 0.66), 0.43 (95% CI: 0.31 to 0.62), 0.37 (95% CI: 0.25 to 0.55), 0.43 (95% CI: 0.29 to 0.63), and 0.19 (95% CI: 0.08 to 0.5), respectively, when compared with the control groups. The severity of POST also reduced significantly (mean difference [MD] -16.43 mm, 95% CI: -21.48 to -11.38) at 1 h and (MD -10.22 mm, 95% CI: -13.5 to -6.94) at 24 h. Both alkalinized and non-alkalinized lidocaine in the subgroup analyses showed significant benefits in emergence phenomena prevention compared with the control. Conclusion Our results indicate that both alkalinized and non-alkalinized intracuff lidocaine may prevent and alleviate POST and postintubation-related emergence phenomena.